Design Thinking Learning Model on Digital Workspace for Sustainable Products and Services to Enhance Digital Entrepreneurs (DTLDW-SPSEDE Model) - Kitsadaporn Jantakun; Thiti Jantakun; Siranan Boonyapalanant; Surachet Channgam; Kanokrat Jirasatjanukul; Ekkharin Srilaphat; Thada Jantakoon (Journal of Educational Issues, 2024)
This study aims to: (1) a design for design thinking learning model on digital workspace for sustainable products and services to enhance digital entrepreneurs; and (2) evaluate the design thinking learning model on digital workspace for sustainable products and services to enhance digital entrepreneurs. The sample is made up of ten specialists who were chosen using purposive sampling. The instrument used in the study was an evaluation form of the leaning model. The arithmetic mean and standard deviation were employed in the investigation. The results show that: (1) the design thinking learning model on digital workspace for sustainable products and services to enhance digital entrepreneurs consists of four key components: 1) Design thinking process, 2) Digital Workspace, 3) Design thinking tools and 4) Sustainability metrics. (2) All ten specialists agreed that the design thinking learning model on digital workspace for sustainable products and services to enhance digital entrepreneurs designed through this study shows the highest level of appropriateness.